2012
DOI: 10.1002/ajmg.a.35444
|View full text |Cite
|
Sign up to set email alerts
|

Acro‐cardio‐facial syndrome: A microdeletion syndrome?

Abstract: Acro-cardio-facial syndrome (ACFS) is an infrequently reported, variable condition characterized by split-hand and split-foot malformation and congenital heart defect (CHD), along with cleft lip and palate, genital anomalies, unusual face and intellectual disability. An autosomal recessive pattern of inheritance has been suggested because of affected sibs born to unaffected parents and parental consanguinity; the cause is unknown. We describe a newborn with the clinical manifestations of ACFS in whom a deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…More importantly, while Prdm1 −/− is embryonic lethal, conditional Sox2 -Cre-driven deletion of Prdm1 results in a number of anomalies including TA, the same CHD we observe in the patient with haploinsufficiency for PRDM1 that we report here 41. Furthermore, a patient with TA was reported to have de novo deletion on 6q with the following coordinates 106 543 543–119 109 372 42. When combined with our deletion, we can determine the critical deletion interval for TA phenotype to be 106 543 543–10 773 7955, which still includes PRDM1 (among others).…”
Section: Discussionsupporting
confidence: 76%
“…More importantly, while Prdm1 −/− is embryonic lethal, conditional Sox2 -Cre-driven deletion of Prdm1 results in a number of anomalies including TA, the same CHD we observe in the patient with haploinsufficiency for PRDM1 that we report here 41. Furthermore, a patient with TA was reported to have de novo deletion on 6q with the following coordinates 106 543 543–119 109 372 42. When combined with our deletion, we can determine the critical deletion interval for TA phenotype to be 106 543 543–10 773 7955, which still includes PRDM1 (among others).…”
Section: Discussionsupporting
confidence: 76%
“…A microdeletion at the 6q21-q22 region has been reported in a patient with this condition [Toschi et al, 2012]. Autosomal recessive inheritance is likely.…”
Section: Syndromal Shfmmentioning
confidence: 90%
“…However, its role in causing SHFM is not clear, as SNX3 mutations have not been identified in other patients with syndromal SHFM and overlapping clinical features [Kumar et al, 2007]. A 12.5 Mb deletion at 6q21-q22.31 that included SNX3 was recently identified in a patient with the acro-cardio-facial syndrome [Toschi et al, 2012]. The 6q16-q22 region was also suggested as a candidate SHFM locus based on a statistical analysis of patients reported in the Human Cytogenetic Database [Niedrist et al, 2009].…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…In the past, autosomal recessive inheritance has been suggested following observation of parental consanguinity and affected siblings in few families [Guion-Almeida et al, 2000; Mingarelli et al, 2005; Digilio and Dallapiccola, 2010]. More recently Toschi et al [2012] proposed that ACFS may be a new microdeletion syndrome based on a 6q21–22.3 microarray deletion identified in an affected child. The authors reviewed reported cases of chromosome deletions in the 6q region, and found the clinical spectrum of anomalies consistent with ACFS [Toschi et al, 2012].…”
Section: To the Editormentioning
confidence: 99%